The new reporting obligation for Respiratory Syncytial Virus (RSV) in Germany - a critical view - Heudorf, Ursel; Marcic, Anne; Steul, Katrin Simone (German Medical Science GMS Publishing House, 2024)
Background: In summer 2023, mandatory reporting of respiratory syncytial virus (RSV) by name was introduced in Germany. The stated objectives were:Methods: These objectives are examined against the background of data from mandatory reporting of RSV in the German federal state of Saxony, which has been required since 2002, and the data from the ARE (acute respiratory diseases) survey in Germany, consideringResults and discussion: An extrapolation of the previously reported data from Saxony to the whole of Germany shows that over 100,000 reports per year must be expected (more than the reports of both rota and noroviruses together). Neither the requirements of the EU Commission nor the views of an expert group of the ECDC recommend mandatory RSV reporting. Mandatory reporting by name is also not appropriate from a legal perspective. A sentinel, which is also better suited to assessing vaccinations, would be more appropriate to avoid unnecessarily overburdening the health authorities. In addition, initial experience with wastewater sentinels for RSV has shown that they may be used to record local and regional RSV infections - albeit without information on the severity of the disease and thus the burden on the healthcare system.Against this background, mandatory reporting of RSV does not appear to be appropriate. Instead, the existing sentinels should be continued and further expanded, possibly supplemented by RSV wastewater monitoring.